Improving skills and their use in Germany - Fuentes Hutfilter, Andrés (OECD Economics Department Working Papers, 2018)
Cognitive skills, such as reading and numeric skills, are key determinants of wages, employment and long-term economic growth. Good cognitive skills also reduce poverty risk and improve non-material wellbeing, such as health and social cohesion. Non-cognitive skills, such as skills to use information and communication technology as well as managerial skills, also help workers adapt to new technologies and globalisation. In Germany cognitive skills among adults are above OECD average, but weaker than in leading economies, especially among individuals with low and middle qualifications. Much progress has been made to improve learning outcomes of youth with disadvantaged socio-economic background. Nonetheless, high-quality childcare, early childhood and full-day primary education still need to expand. The vocational education system is very successful in integrating young people well in the labour market. Strengthening general education within the successful vocational education and training system could help ensure the capacity of graduates to adapt to technological change at higher age in the future. Participation in life-long learning could be encouraged by better addressing individual training needs. This could improve prospects for adults without professional qualifications. Women's skills are used less well than men's, calling for policies to address gender imbalances in the labour market. This Working Paper relates to the 2018 OECD Economic Survey of Germany (http://www.oecd.org/eco/surveys/economic-survey-germany.htm)